Evaluation of the Association of VDR rs2228570 Polymorphism with Elite Track and Field Athletes’ Competitive Performance - ULUCAN, KORKUT (My University, 2023)
The present study aimed to examine the vitamin D receptor (VDR), rs2228570 polymorphism, and its effect on elite athletes’ performance. A total of 60 elite athletes (31 sprint/power and 29 endurance) and 20 control/ physically inactive, aged 18–35, voluntarily participated in the study. The International Association of Athletics Federations (IAAF) score scale was used to determine the performance levels of the athletes’ personal best (PB). Whole exome sequencing (WES) was performed by the genomic DNA isolated from the peripheral blood of the participants. Sports type, sex, and competitive performance were chosen as the parameters to compare within and between the groups by linear regression models. The results showed no statistically significant difference between the CC, TC, and TT genotypes within and between the groups (p > 0.05). Additionally, our results underlined that there were no statistically significant differences for the association of rs2228570 polymorphism with PBs within the groups of the (p > 0.05) athletes. The genetic profile in the selected gene was similar in elite endurance, sprint athletes, and in controls, suggesting that rs2228570 polymorphism does not determine competitive performance in the analyzed athlete cohort.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Medicine; Internal Medicine Sciences; Family Medicine; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Klinik Tıp (MED); Klinik Tıp; TIBBİ BİLİŞİM; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICAL INFORMATICS; HEALTH CARE SCIENCES & SERVICES; Liderlik ve Yönetim; Sağlık Politikaları; Tıbbi Bilişim; Sağlık Bilgi Yönetimi; Leadership and Management; Health Policy; Health Informatics; Health Information Management; athletics; endurance athletes; rs2228570 polymorphism; sprint/power athletes; VDR